Capacity Estimation of the Very Short-Range Electromagnetic Underwater Channel Based on Measurements - Jesús López-Fernández; Unai Fernández-Plazaola; Jose F. Paris (International Journal of Antennas and Propagation)
The significant attenuation experienced by electromagnetic waves in sea water is the main reason why acoustic waves are generally preferred in underwater communication. Nevertheless, acoustic waves have various drawbacks. For example, they are negatively affected by factors such as mechanical noise, slow propagation speed, and, particularly, low bandwidth, which leads to digital links at a lower bit rate. However, in short-range links, these problems can be overcome by reconsidering the use of electric current communications. For instance, data collected by remote-control vehicles in offshore oil and gas and renewable energy plants can be transmitted at distances of even 1 m or less. This study uses previous frequency response measurements taken in deep water to explore the capacity of a short-range electromagnetic underwater channel. Because of water movement, the nonstatic position of the vehicle when the transmission occurs means that the channel is regarded as randomly time-variant. A statistical model is proposed and the ergodic capacity is calculated for a 7 MHz bandwidth channel at distances ranging from 0.5 m to 5 m as well as for different values of transmitter power. The results of this study reflect capacity values of tens of kbps at distances of approximately 5 m to several Mbps at distances of less than 1.5 m.